(untitled) (Indian Journal of Arid Horticulture, 2013)
Due to the environmental pollution, residue in soil water and food materials and effect on non-target organism, the use of chemical fungicides for disease management is being discouraged in the present day crop production. The opening up of the global economy has enhanced the possibility of fruit-export. The fruit-exporting countries have strict requirements to meet health standards. These requirements have adversely affected the fungicide application on harvested fruits. Fortunately, the search for alternative treatments has yielded positive results with heat, plant extracts, radiation and some chemicals. Of these strategies, the use of plant extracts has proved safer and effective against certain diseases of harvested fruits. This investigation reports findings on efficacy of leaf extracts of Tulsi , Sadabahar , Parthenium , Turmeric and Ginger against important fruit rots of mango and citrus fruits. Application of leaf extract of Tulsi (10%) reduced disease severity and spore germination of Rhizopus rot, Penicillium rot and Botryodiplodia rot of mango and citrus fruits.